Current status of countermeasures for infectious diseases and resistant microbes in the field of urology. (5th August 2019) - Kitano, Hiroyuki; Teishima, Jun; Shigemura, Katsumi; Ohge, Hiroki; Fujisawa, Masato; Matsubara, Akio
Abstract: A worldwide increase in antimicrobial‐resistant microbes due to the improper use of antimicrobial agents, along with a lack of progress in developing new antimicrobials, is becoming a societal problem. Although carbapenem‐resistant Enterobacteriaceae, which are resistant to carbapenem antimicrobials, first appeared in 1993, treatment options remain limited. Mechanisms behind antimicrobial resistance involve changes to microbial outer membranes, drug efflux pump abnormalities, β‐lactamase production and the creation of biofilms around cell bodies. Genetic information related to these forms of antimicrobial resistance exists on chromosomes and plasmids, and when located on the latter can easily be transmitted to other strains, no matter the species, which creates a risk of antimicrobial resistance spreading exceptionally rapidly. To prevent the spread of antimicrobial resistance, the World Health Organization in 2015 published an action plan on antimicrobial resistance, based on which World Health Organization member countries have laid out specific policies and targets. Urinary tract infections are a type of healthcare‐associated infection, and the sexually transmitted disease pathogen, Neisseria gonorrhoeae, has been included in a list of microbes that pose a risk to human health published by the US Centers for Disease Control and Prevention. Urologists face numerous problems when attempting to use antimicrobials properly, which is one method of dealing with antimicrobial resistance. Therefore, this article describes the current state of resistant microbes associated with urinary tract infections and countermeasures for antimicrobial resistance, including new antimicrobials.